THE EFFECTS OF PRE-SOWING TREATMENTS WITH ALLELOPATHIC PLANT AQUEOUS EXTRACTS ON GERMINATION PARAMETERS OF AGED SOYBEAN SEEDS - Mamlić (Miladinov), Zlatica J (Journal of Agricultural Sciences (Belgrade), 2024)
The aim of the paper was to examine the allelopathic influence of aqueous extracts of herbs and medicinal plants on the quality parameters of aged soybean seeds. The research was carried out at the Institute of Field and Vegetable Crops in Novi Sad, on aged seeds of two soybean varieties, NS Simba and NS Viseris. The seed was 20 months aged. In order to determine the allelopathic effect, the seeds were primed in plant aqueous extracts: geranium (Geranium sinense), dill (Anethum graveolens), andy everlasting (Helichrysum arenarium), creeping thyme (Thymus serpyllum), celery (Apium graveolens), oregano (Origanum vulgare), basil (Ocimum basilicum), lemon balm (Melissa officinalis), rosemary (Rosmarinus officinalis), wormwood (Artemisia absinthium), peppermint (Mentha x piperita), sage (Salvia officinalis), lavender (Lavandula angustifolia). The results showed that it is not possible to talk about the universal application of a particular aqueous extract, because the effect of allochemicals is significantly influenced by the variety. In the variety NS Viseris, all aqueous extracts except Melissa officinalis, significantly reduced GE, GP, and VI. The most negative effect was achieved with the use of Apium graveolens, Thymus serpyllum, and Ocimum basilicum. Apium graveolens and Thymus serpyllum had the greatest impact on quality reduction in the NS Simba variety as well. However, with the NS Simba variety, in addition to the reduction, a significant increase in seed quality was achieved. With the use of Salvia officinalis aqueous extract, GE and GP increased by 13.7% and VI increased by 13.7%, VI by 10.21%. A positive effect was achieved with the use of Melissa officinalis. All aqueous extracts in both cultivars had a significant effect on T50, even the aqueous extracts that had a negative effect on GE and GP.            Key words: allelopathy, aqueous extracts, priming, soybean